DIFFERENT TYPES OF STEREOTYPE TOWARD LGBT AS MINORITY ON AMERICAN ONLINE NEWS - Aprilya Indah R.; Dewi Haryani Susilastuti (Universitas Gadjah Mada, 2020)
This research discusses the stereotypes of LGBT in the United States, which appear on American online news. This research works under Post-Nationalist American Studies by applying the gender socialization approach and stereotype theory. Qualitative research aims to seek the differences of stereotypes experienced by LGBT in the United States. The online news portals selected include The New York Times, Washington Post, and USA Today. These news portals are chosen due to their neutrality and trustworthiness as online news portals for American society. By examining the data, the researcher found that the stereotypes experienced by Lesbian, Gay, Bisexual, and Transgender in the United States are different from one another. The findings and discussion show that Transgender stereotypes in the United States are more negative rather than others. In short, LGBT is mostly considered as a unity; however, it faces different challenges due to their minority status in the middle of American society.